1998
DOI: 10.3109/14756369809035823
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Bisbenzylisoquinoline Alkaloids are Inhibitors of Trypanothione Reductase

Abstract: Eleven bisbenzylisoquinoline (BBIQ) alkaloids were studied for in vitro trypanocidal activity against trypomastigote forms of the Y strain of Trypanosoma cruzi. The inhibitory activity of these compounds against trypanothione reductase (TR), a target enzyme for chemotherapy against Chagas disease, was also studied. Six BBIQ alkaloids (antioquine, cepharanthine, daphnoline, limacine, cycleanine and (-) curine) displayed a 50% lethal concentration (LC50) against T. cruzi of less than 100 microM. Daphnoline and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
0
35
0
1
Order By: Relevance
“…Se ha reportado que el extracto de la hoja de B. dracunculifolia, a una concentración de 3 mg/mL, produjo 100% de lisis de formas tripomastigotes de T. cruzi (13) ; los extractos y fracciones de A. amazonicus mostraron lisis de las formas tripomasigotes de T. cruzi in vitro (14) ; otros investigadores también han demostrado el efecto tripanocida de diversos extractos vegetales (10,15,16) , así como de diversas estructuras terpénicas contra uno o todos los estadíos de T. cruzi (17)(18)(19)(20) . También han mostrado efecto tripanocida algunos alcaloides (21)(22)(23) , flavonoides (24)(25)(26) , lignanos (27) y artemisininas (28) .…”
Section: Discussionunclassified
“…Se ha reportado que el extracto de la hoja de B. dracunculifolia, a una concentración de 3 mg/mL, produjo 100% de lisis de formas tripomastigotes de T. cruzi (13) ; los extractos y fracciones de A. amazonicus mostraron lisis de las formas tripomasigotes de T. cruzi in vitro (14) ; otros investigadores también han demostrado el efecto tripanocida de diversos extractos vegetales (10,15,16) , así como de diversas estructuras terpénicas contra uno o todos los estadíos de T. cruzi (17)(18)(19)(20) . También han mostrado efecto tripanocida algunos alcaloides (21)(22)(23) , flavonoides (24)(25)(26) , lignanos (27) y artemisininas (28) .…”
Section: Discussionunclassified
“…Cepharanthine (compound 14) S81 was the most potent TR inhibitor within this group of compounds with K i and K i ¢ values of 7.6 and 51.6 lM, respectively (Fournet et al 1998). Subsequent studies on the efficacy upon oral treatment of Balb/c mice acutely and chronically infected with T. cruzi yielded promising results for daphnoline but not for the excellent TR inhibitor cepharanthine (Fournet et al 2000).…”
Section: Mixed-type Inhibitorsmentioning
confidence: 96%
“…Previous studies have reported that BBIQ alkaloids act on the trypanothione reductase (a pathogen-specific enzyme which is one of the main targets in the search for new drugs against T. cruzi) similarly to other inhibitors of this enzyme (nitrofurans and naphthoquinones), which have a positive charge attached to a hydrophobic group. The enzyme is inhibited when binding occurs, interfering with catalysis of trypanothione disulfide reduction (the compound responsible for oxygen exchange), the level of oxygen in the parasite is reduced, and death occurs (Fournet et al 1998). …”
Section: Identification and Effects Of Mixtures And Isolated Compoundsmentioning
confidence: 98%